Socialization of Cash Waqf Literacy as a Waqf Solution For Millennial Generation Students in Kulon Progo Regency - Ifan Agung Pambudi; Hediantoro Hediantoro; Dita Widyaningrum; Rizky Surya Saputra; Nafis Sholikhah; Aulia Nurul Safitri; Febrian Yena Remalia; Chilmi Syafiq Mashum; Choirul Arifah; Mellyana Alvi Purniaji; Fikri Anam; Sakina Tulaulia; Shafa Yulita Salma Nafisa; Nurul Imtiqomah (Journal of Islamic Economy and Community Engagement, 2022)
The socialization entitled